2018
DOI: 10.1177/0361198118793276
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Tensile Test (IDT) to Determine Asphalt Mixture Performance Indicators during Quality Control Testing in New Jersey

Abstract: In recent years, there has been a growing interest in incorporating performance testing during the mixture design and quality control testing of asphalt mixtures. The move toward utilizing performance related specifications (PRS) and balanced mixture design concepts have pushed the need for asphalt mixture performance testing to the forefront. Numerous researchers have proposed a variety of laboratory tests that have showed promise at predicting asphalt mixture performance, yet most of these test methods are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The post-peak slope is defined by the tangent slope at 75% of the peak load on the post-peak curve (𝑚 % ) (Equation ( 2)). Higher CTIndex demonstrates better resistance to cracking [42,57,58]. The HI-IDTStrength is an expression of the standardization of the maximum applied load (P100%) in relation to the configuration of the specimen (i.e., diameter (D) and height (t)) (Equation ( 3)).…”
Section: Performance Assessment Indicatorsmentioning
confidence: 99%
“…The post-peak slope is defined by the tangent slope at 75% of the peak load on the post-peak curve (𝑚 % ) (Equation ( 2)). Higher CTIndex demonstrates better resistance to cracking [42,57,58]. The HI-IDTStrength is an expression of the standardization of the maximum applied load (P100%) in relation to the configuration of the specimen (i.e., diameter (D) and height (t)) (Equation ( 3)).…”
Section: Performance Assessment Indicatorsmentioning
confidence: 99%
“…specimens are tested at intermediate ambient temperatures (5 °C-35 °C, depending on local climate) and a loading rate of 50 mm/min. Moreover, it is easy to perform since no cutting, gluing, notching, drilling, or instrumentation required [60,61]. Figure 6 illustrates the testing configuration for ITS and CT tests (Table 4).…”
Section: Cracking Tolerance Index (Ct-index)mentioning
confidence: 99%
“…The IDEAL-CT test is sensitive to the composition of the asphalt concrete mixture and has been carried out at the State Departments of Transportation and in the contractors’ laboratories in the United States. Compared with the above seven concrete cracking test methods, the IDEAL-CT method can be easily implemented with the following advantages: no instrumentation, cutting, gluing, drilling, or notching of specimens) and practicality (minimum training needed for routine operation), and repeatability (coefficient of variance less than 25%) [ 3 , 4 ]. It is also reported that the CT Index measured in the IDEAL-CT test correlated well with the field performance in terms of fatigue cracking from the FHWA accelerated loading facility full-scale testing.…”
Section: Introductionmentioning
confidence: 99%